Performance assessment of Crosses between Gadam and Hardcore Tannin sorghum in hybrid lines production - Shinda, Cecilia A.; Gitari, Josiah N.; Nthakanio, Paul N.; Runo, Steven; Gichimu, Bernard M.; Maina, Samuel (My University, 2022)
Gadam cultivar of sorghum has been characterized by low yields compared to the international yield levels of sorghum. In this research, Gadam was crossed with Serena, Seredo, and Kari/Mtama-1 in an attempt to increase yield through heterosis. The objective of this study was to determine the level of compatibility and heterosis in crosses between Gadam and the three sorghum lines in a reciprocal crossing. Gadam was crossed with the three lines and their reciprocals to make six treatments that were subjected to compatibility and heterosis tests. The F1 hybrid lines and their parental controls were sown in a randomized complete block design in three replicates. Compatibility and heterosis data variances were analyzed using R statistical software. The cross between Gadam x Serena, Serena x Gadam and the parent Gadam exhibited moderate mean plant height ranging from 99.5 cm to 120.5 cm. The cross Gadam x Serena recorded a desirable negative mid-parent heterosis of -19.89 and -16.16 for plant height and days to maturity respectively. All F1 hybrids recorded positive mid-parent heterosis for the panicle length, the number of reproductive tillers, a thousand seed weight, and the number of tillers per plant. The crosses Gadam x Seredo, Seredo x Gadam, Gadam x Serena and Kari/Mtama-1 x Gadam recorded significantly lower grain filling percentages compared to their parents. In conclusion, the F1 hybrids differed significantly from their reciprocal crosses especially in days of heading, flowering, and maturity indicating a significant maternal influence in these traits. Also, the mid-parent and better parent heterosis had a nonsignificant difference in quantitative traits assessed except for the plant height and grain filling percentage.
Keywords: Compatibility; Fhybrid lines; Gadam sorghum; Heterosis; Maternal influence